The Difference in Clinical Reasoning Competence between Pre-Clinical Students and Clinical Students on Pediatric Tropical Disease Cases - Pujiati, Pujiati Abbas (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2015)
Introduction: Clinical reasoning is a thinking process happened when various informations gathered from clinical cases were given or met by medical students, and used for formulating diagnosis and solving patients problems. Experiences and material inputs are important factors affecting clinical reasoning. Various theories explained that students on pre-clinical and clinical rotation level are still on the novice stage, so it is possible to have similar stage on clinical reasoning. On the other hand, it was reported that there are differences in clinical reasoning on different academic stages. Objective: knowing the differences of clinical reasoning on preclinical students and clinical students.Method: observational study with cross sectional design. Respondents of this study were 120 students from medicine faculty of Sultan Agung Semarang University, comprised of: 60 preclinical students whom have been underwent tropical disease modul batch 2011 and 60 clinical rotation students on pediatric stage. Respondents answered 20 items questions in Script Concordance Test (SCT) form on pediatric tropical disease cases. SCT items were prepared by pediatricians, structures and contents were reviewed by medical education experts and concordanced by 10 experts of pediatric unit. Value differences between 2 groups were statistically analyzed using Mann Whitney U on SPSS 16.0, with acceptable error accepted level if p<0.05. Result: non parametric result test by Mann-whitney showed that mean score of SCT on preclinical group were lower (8,57;+ 1,81) than on clinical rotation students 11,49 (+ 1,98) p = 0,000. Conclusion: clinical reasoning competence measured by SCT is higher on clinical rotation students compared to pre clinical students.